EVOLUTION OF SUSTAINABILITY ACCOUNTING: IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS AND ITS IMPACT ON BUSINESS SUSTAINABILITY - Franco Benony Limba; Shella Gilby Sapulette (Adisam Publisher, 2024)
The use of accounting allows for good financial management, where good financial management in a business will of course have more potential for the sustainability of a business. Accounting is a powerful tool that plays a central role in achieving business sustainability goals. Financial accounting standards act as a compass that directs the flow of financial information so that it remains on the correct and trustworthy path. Implementation of sustainable financial accounting standards has a positive impact on business sustainability, both in terms of financial transparency and support for sustainable development goals. This research in-depth investigates the evolution of sustainability accounting: the implementation of financial accounting standards and its impact on business sustainability using literature study methods. This research discusses the evolution of sustainability accounting, the definition and types of financial accounting standards, accounting as the main tool in realizing sustainable business, the implementation of financial accounting standards and its impact on business sustainability.